The Phonology And Morphology Of Yemeni Tihami Dialect: An Autosegmental Account - Kassin, Tajul Aripin (2010)

(untitled)
Tidak banyak kajian metodologi tentang dialek Arab, terutamanya dialek Arab Yemen (YAD) (Versteegh, 1997).